Implementasi Nilai Keteladanan Dalam Pendidikan Karakter di Sekolah Dasar - Eva Farkha N; Lilik Maftuchah; Siti Khumairiyah; Mustadi; Ida lutfiyatul Jamilah; M. Mahbub; Lestari Widodo (Pascasarjana Universitas Qomaruddin, 2025)
This study aims to examine the implementation of exemplary values in character education at the elementary school level. Character education is a crucial component in shaping students' personalities, and role modeling is considered one of the most effective methods, as children tend to imitate the behavior of figures they admire, such as teachers and parents. In the context of Indonesian education, exemplary behavior is seen as a powerful means to instill moral values such as honesty, responsibility, discipline, and tolerance, which are essential for life in society. This research employs a library research method with a qualitative descriptive approach. Data were collected from various literature sources, including books, academic journals, and educational policy documents related to character education and role modeling. The collected data were then analyzed to identify basic concepts, field implementation practices, and the challenges in integrating exemplary values into the learning process. The findings reveal that role modeling significantly influences the internalization of character values in students. Teachers' daily behavior and attitudes, along with active involvement from parents at home, play a crucial role in shaping children's character. Furthermore, character education integrated into both the formal curriculum and extracurricular activities strengthens the development of those values. Therefore, collaboration between schools, families, and the broader community is key to the successful implementation of character education based on exemplary practices.